Pengaruh Product Quality, Price, Dan Promotion Terhadap Customer Loyalty Melalui Customer Satisfaction Pada Konsumen Mie Cetar Di Malang. - Adelia Dwi Wulandari; Eka Farida; Nanik Wahyuningtyas (E-JRM : Elektronik Jurnal Riset Manajemen, 2026)
Abstract The purpose of this research is to investigate the impact of product quality, price, and promotion on customer loyalty through customer satisfaction among Mie Cetar consumers in Malang. A quantitative approach was employed using a survey method involving 110 respondents. Data were collected through questionnaires and analyzed using Partial Least Square–Structural Equation Modeling (PLS-SEM). The results indicate that product quality and promotion have a significant effect on customer loyalty, while price does not have a direct effect. Furthermore, product quality, price, and promotion significantly influence customer satisfaction. Customer satisfaction mediates the effect of product quality and price on customer loyalty, but does not mediate the effect of promotion on customer loyalty. These findings highlight the importance of maintaining product quality and appropriate pricing strategies to improve customer satisfaction and loyalty in the culinary MSME sector. Keywords: Product Quality, Price, Promotion, Customer Satisfaction, Customer Loyalty